2022
DOI: 10.1111/mpp.13181
|View full text |Cite
|
Sign up to set email alerts
|

FKBP‐type peptidyl‐prolyl cis‐trans isomerase interacts with the movement protein of tomato leaf curl New Delhi virus and impacts viral replication in Nicotiana benthamiana

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…(2015) showed that a serine/threonine kinase domain protein encoded by OsPBL1 gene might play a role in rice stripe resistance. Chang et al. (2022) found a FKBP-type peptidyl-prolyl cis-trans isomerase (PPIase) could interact with the motor protein of Tomato leaf curl New Delhi virus , and its transient overexpression reduced the virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) showed that a serine/threonine kinase domain protein encoded by OsPBL1 gene might play a role in rice stripe resistance. Chang et al. (2022) found a FKBP-type peptidyl-prolyl cis-trans isomerase (PPIase) could interact with the motor protein of Tomato leaf curl New Delhi virus , and its transient overexpression reduced the virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the isolates of ToLCNDV are not mechanically transmitted to their host plants. There is a single isolate known as ToLCNDV oriental melon (OM), which was originally isolated from an infected oriental melon plant, can be mechanically transmissible (Chang et al, 2022) and this transmission is demonstrated to be associated with the movement protein (MP) of DNA-B. A multifunctional protein called viral MP helps viruses spread from cell to cell and throughout the body.…”
Section: Transmission Methodsmentioning
confidence: 99%
“…The preparations of the infectious clones of ToLCNDV-CB, ToLCNDV-OM, ToLCTV, and TYLCTHV were carried out as described in our previous studies (Chang et al, 2010;Tsai et al, 2011;. Agroinfiltration was conducted with a previously described method (Chang et al, 2022), with some modifications. A single colony was picked and cultured overnight at 28°C in 4 ml of lysogeny broth (LB) media supplemented with appropriate antibiotics (50 mg/ml kanamycin for infectious clones of ToLCNDV-CB DNA-A and DNA-B, TYLCTHV DNA-A and DNA-B, ToLCTV and ToLCNDV-OM DNA-B and 50 mg/ml gentamycin for ToLCNDV-OM DNA-B).…”
Section: Agroinfiltration and Virus Inoculum Preparationmentioning
confidence: 99%